ПОДГОТОВКА КАДРОВ В ОБЛАСТИ УПРАВЛЕНИЯ ЗЕМЕЛЬНЫМИ РЕСУРСАМИ: СОВРЕМЕННОЕ СОСТОЯНИЕ - Курманова, Г К (Journal of Economic Research & Business Administration, 2015)
Recently the requirement for preparation of the highly skilled experts capable quickly to react to innovations has increased in Kazakhstan, and also to introduce new methods and approaches for maintenance of competitiveness of national economy. And only the high schools focused on an innovative way of development, can realize problems of the President of the country on creation of innovative economy and correspond to high standards of tomorrow.